On the rhenium segregation at the low angle grain boundary in a single crystal Ni-base superalloy. (August 2020) - He, Junyang; Scholz, Felicitas; Horst, Oliver Martin; Thome, Pascal; Frenzel, Jan; Eggeler, Gunther; Gault, Baptiste
Abstract: Industrial scale single crystal (SX) Ni-base superalloys contain numerous low angle grain boundaries inherited from the solidification process. Here, we demonstrate that low angle grain boundaries in a fully heat-treated SX model Ni-base superalloy are strongly segregated with up to 12 at% Re. Some Re-rich dislocations forming this grain boundary are found located inside γ, others close to a γ/γ′ interface. Although these segregated Re atoms lose their solid-solution strengthening effect, they may enhance the creep resistance by pinning the low angle grain boundaries and slowing down dislocation reactions. Graphical abstract: Image, graphical abstract